2018
DOI: 10.1002/dneu.22624
|View full text |Cite
|
Sign up to set email alerts
|

Eph Receptor Effector Ephexin Mediates Olfactory Dendrite Targeting in Drosophila

Abstract: Deciphering the mechanisms of sensory neural map formation is a central aim in neurosciences. Failure to form a correct map frequently leads to defects in sensory processing and perception. The olfactory map develops in subsequent steps initially forming a rough and later a precise map of glomeruli in the antennal lobe (AL), mainly consisting of olfactory receptor neuron (ORN) axons and projection neuron (PN) dendrites. The mechanisms underpinning the later stage of class-specific glomerulus formation are not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Olfactory sensory neurons located on the antennae or palps connect to projection neurons (PNs) in the antennal lobe. These connections are highly stereotyped across individuals [9][10][11][12][13] . Expectedly, the responses of PNs to odors are also stereotyped 14,15 .…”
mentioning
confidence: 99%
“…Olfactory sensory neurons located on the antennae or palps connect to projection neurons (PNs) in the antennal lobe. These connections are highly stereotyped across individuals [9][10][11][12][13] . Expectedly, the responses of PNs to odors are also stereotyped 14,15 .…”
mentioning
confidence: 99%
“…As described above, Vav physically binds to the Eph receptor in Drosophila S2 cells. This receptor is known to play a critical role in a wide range of neuronal processes, including local dendrite branch dynamics, axon navigation, and synapse formation in Drosophila (Anzo et al, 2017; Boyle et al, 2006; Frank et al, 2009; Sardana et al, 2018). We thus sought to investigate whether Eph controls dendritic outgrowth in the aCC motoneurons.…”
Section: Resultsmentioning
confidence: 99%
“…(ARHGEF5/TIM1), Ephexin4 (ARH GEF16), and Ephexin5 (ARHGEF15/Vsm-RhoGEF) 9,21,[29][30][31][32] . It has been reported that Ephexin1 and Ephexin5 are phosphorylated by Src or Eph receptors but not ARH-GEF16 21,29,33 .…”
Section: Discussionmentioning
confidence: 99%